Green Synthesis of Heterocycles - Arico, Fabio; Reiser, Oliver (Frontiers Media SA, 2020)
Heterocycles are among the most common scaffolds in many organic molecules, e.g., vitamins, hormones, antibiotics, alkaloids, herbicides, dyes, drugs, and pharmaceutically relevant substances. These molecules are also incorporated in numerous macromolecules such as DNA, polymers, and macrocycles, where their hetero-functional units are often employed to establish supramolecular interaction. It is thus not surprising that-since the 19th century-the synthesis of heterocycles has been constantly blooming, evolving from classic condensation reactions to the development of click reactions and new multicomponent domino synthetic approaches. In the last thirty years, with the ever-growing research developments of new and atom-efficient sustainable synthetic strategies, the field of Green Chemistry has made significant contributions to the development of heterocyclic motifs. The novel methodologies aim at high process performances by means of eco-compatible methodologies, employing non-toxic and biodegradable chemicals.